The interaction of strigolactones with abscisic acid during the drought response in rice - Haider, I.; Andreo-Jimenez, B.; Bruno, M.; Bimbo, A.; Flokova, K.; Abuauf, H.; Ntui, V.O.; Guo, X.; Charnikhova, T.; Al-Babili, S.; Bouwmeester, H.J.; Ruyter-Spira, C. (Oxford University Press, 2018)
Both strigolactones (SLs) and abscisic acid (ABA) biosynthetically originate from carotenoids. Considering their common origin, the interaction of these two hormones at the biosynthetic and/or regulatory level may be anticipated. Here we show that, in rice, drought simultaneously induces SL production in the root, and ABA production and the expression of SL biosynthetic genes in the shoot. Under control conditions, the ABA concentration was higher in shoots of the SL biosynthetic rice mutants dwarf10 (d10) and d17 than in wild-type plants, while a similar trend was observed for the SL perception mutant d3. These differences were enhanced under drought. However, drought did not result in an increase in leaf ABA content in the rice mutant line d27, carrying a mutation in the gene encoding the first committed enzyme in SL biosynthesis, to the same extent as in the other SL mutants and the wild type. Accordingly, d10, d17, and d3 lines were more drought tolerant than wild-type plants, whereas d27 displayed decreased tolerance. Finally, overexpression of OsD27 in rice resulted in increased levels of ABA when compared with wild-type plants. We conclude that the SL and ABA pathways are connected with each other through D27, which plays a crucial role in determining ABA and SL content in rice.